Mechanism of action of an imidopiperidine inhibitor of human polynucleotide kinase/phosphatase. - Freschauf, G; Mani, R; Mereniuk, T; Fanta, M; Virgen, C; Dianov, G; Grassot, J; Hall, D; Weinfeld, M (2010)
The small molecule, 2-(1-hydroxyundecyl)-1-(4-nitrophenylamino)-6-phenyl-6,7a-dihydro-1H-pyrrolo[3,4-b]pyridine-5,7(2H,4aH)-dione (A12B4C3), is a potent inhibitor of the phosphatase activity of human polynucleotide kinase/phosphatase (PNKP) in vitro. Kinetic analysis revealed that A12B4C3 acts as a noncompetitive inhibitor, and this was confirmed by fluorescence quenching, which showed that the inhibitor can form a ternary complex with PNKP and a DNA substrate, i.e. A12B4C3 does not prevent DNA from binding to the phosphatase DNA binding site. Conformational analysis using circular dichroism, UV difference spectroscopy, and fluorescence resonance energy transfer all indicate that A12B4C3 disrupts the secondary structure of PNKP. Investigation of the potential site of binding of A12B4C3 to PNKP using site-directed mutagenesis pointed to interaction between Trp(402) of PNKP and the inhibitor. Cellular studies revealed that A12B4C3 sensitizes A549 human lung cancer cells to the topoisomerase I poison, camptothecin, but not the topoisomerase II poison, etoposide, in a manner similar to small interfering RNA against PNKP. A12B4C3 also inhibits the repair of DNA single and double strand breaks following exposure of cells to ionizing radiation, but does not inhibit two other key strand-break repair enzymes, DNA polymerase beta or DNA ligase III, providing additional evidence that PNKP is the cellular target of the inhibitor.